Anisotropic crystallization of YAG on the surface of glass by CO2 laser irradiation. Issue 15 (30th March 2022) - Feizbakhsh, Mona; Safari Yazd, Nazila; Keshavarzi, Ashkan; Doosti, Azadeh
Abstract : In this study, we studied the laser process and crystallization of 2D YAG from yttrium aluminosilicate glass. Abstract : In this study, we studied the laser process and crystallization of 2D YAG from yttrium aluminosilicate glass. The anisotropic crystallization of YAG was achieved through a continuous wave (CW) CO2 laser irradiation process. We demonstrated the possibility to synthesize transparent YAG glass-ceramics via laser irradiation in the system Y2 O3 /Al2 O3 /SiO2 doped with Ce 3+ /Bi 3+ /Mn 2+ in glass.